PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEPUTUSAN KEUANGAN DAN NILAI PERUSAHAAN PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurfitri Apriliani; Restu Agusti; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aimed of this study is to investigate the effect of ownership structure to funding decisions, investment decisions, dividend policy and company value. The Sample in this research are 22 companies of the LQ 45 Company in Indonesia Stock Exchaange (IDX) so that the total sample period 2011-2012 amounted to 44 research data. This research uses multiple regression analysis with the SPSS program version 19.0. The result of this study found that managerial ownership have a significant effect on funding decisions, while institutional ownership has no significant effect on funding decisions. Ownership structure have a significant effect on dividend policy and ownership structure have a significant effect on company value. The magnitude of the effect managerial ownership on funding decisions is equal to -0,975. The magnitude of the effect institutional ownership and managerial ownership on dividend policy is equal to -1,818 and -0,04. While the magnitude of the effect institutional ownership and managerial ownership on company value is 1,772 and 0,202.Keywords: Funding Decisions, Investment Decisions, Dividend Policy, Company Value, Institutional Ownership and Managerial Ownership.